Comparison of the hypotensor effect between latanoprost versus selective laser trabeculoplasty obtained with the water drinking test - Germano,Renato Antunes Schiave (2021)
ABSTRACT Purpose: Glaucoma is the main cause of irreversible blindness worldwide. Peak intraocular pressure is one of the main risk factors for glaucoma progression, and intraocular pressure reduction remains the only therapeutic strategy for all types of glaucoma. The main purpose of our study was to compare the baseline and peak intraocular pressure reduction obtained with the water drinking test between the two eyes of the same patients using 0.005% latanoprost in one eye and selective laser trabeculoplasty application in the contralateral eye. Methods: This was a prospective, interventional, longitudinal, and randomized clinical trial, in which 30 consecutive glaucomatous patients, medically controlled using latanoprost monotherapy, were recruited from a single ophthalmological center. The patients’ eyes were randomized, and one eye was selected for SLT treatment and topical 0.005% latanoprost was introduced in the contralateral eye. The baseline intraocular pressure and peak intraocular pressure were evaluated 1 month (water drinking test 2) and 6 months (water drinking test 3) after treatment. Results: There was no significant difference between the mean pre-washout intraocular pressure in the randomized eyes for selective laser trabeculoplasty and latanoprost (13.6 ± 2.1 and 13.3 ± 1.8 mmHg, respectively; p=0.182). Regarding baseline intraocular pressure, there was no significant difference in the water drinking test 2 (p=0.689) and water drinking test 3 (p=0.06) between the groups. There was no significant difference in the intraocular pressure peak between the SLT and latanoprost groups at water drinking test 2 (p=0.771) or water drinking test 3 (p=0.774). Conclusions: The intraocular pressure reduction efficacy is similar between latanoprost and selective laser trabeculoplasty. Glaucomatous patients who are medically controlled with latanoprost and switch treatment to selective laser trabeculoplasty maintain control of intraocular pressure.